Qualitative study of patients with metastatic prostate cancer to adherence of hormone therapy. (February 2019) - Iacorossi, Laura; Gambalunga, Francesca; De Domenico, Rosaria; Serra, Valeria; Marzo, Cristina; Carlini, Paolo
Abstract: Purpose: To explore adherence to oral hormone treatment in patients with metastatic prostate cancer (mCRPC) and to identify the factors that influence it. Methods: A qualitative exploratory study was conducted at the National Cancer Institute of Rome. Patients aged >18 years with castration-resistant prostate cancer (mCRPC) and who were using oral hormone drugs were recruited. Semi-structured interviews were used for data collection, subsequently transcribed verbatim and analysed using Ritchie and Spencer's framework analysis. Results: The sample included 13 patients with a median age of 72 who were treated, on average, for seven months with abiraterone acetate (AA) (76.9%) and enzalutamide (ENZ) (23.1%). Five themes were identified: expression of the concept of adherence, favouring factors, obstacle factors, functional strategies and levels of adherence. Conclusions: The patients express a good level of adherence, which they define in different ways—the helping relationship with the attending physician, the support of the family members and the few side effects of the drugs. For the future, it is recommended to perform a multicentre mixed method study to explain the levels of adherence and distress in women with breast cancer. Highlights: Patients give different meanings to the concept of adherence. Patients, despite having a medium-high age, expressed a good level of adherence to hormonal treatment. Favoring factors of adherence are the information received from the healthcare staff, the support of family members and the few side effects related to treatment. Obstructive factors of adherence are polytherapy, drug size and procurement.